Crossed aldol reactions in water using inexpensive and easily available materials as a tool for reaction optimization teaching in an undergraduate organic chemistry laboratory - Ruiz Criollo, Kevin Alexander (2020)
Crossed aldol reactions are aldol reactions that involve two different types of carbonyl compounds, which depending on the involved compounds, can be useful or not in organic synthesis. This type of reaction can be a difficult topic in lectures and laboratories for undergraduate chemistry students because several rules need to be considered in order to predict the product. In this work, an article for the Journal of Chemical Education about aqueous crossed aldol reactions of vanillin and cinnamaldehyde as experiments with inexpensive and easily available reagents to obtain dehydrozingerone and cinnamylidene acetone products respectively is presented. In the vanillin condensation, optimization reaction is implicated with the use of LiCl or NiCl2 additives as catalysts, and its reaction ratio is controlled by thin-layer chromatography. While in the cinnamaldehyde condensation, the use of inexpensive materials and non-toxic solvents are advantages to carry out a reliable and straightforward procedure. Additionally, the goal for this work is to reach the learning outcomes for students, such as in improving the students’ lab decision making and time management skills. Finally, the use of analytical techniques for the characterization of final products helps the students to reinforce their knowledge in the analysis of organic compounds.